Development of a scaffold displaying exoloops of RXFP1 - Diepenhorst, Natalie A.; Gooley, Paul R.; Stone, Martin J.; Bathgate, Ross A.D. (Italian Journal of Anatomy and Embryology, 2014)
Relaxin family peptide receptor 1 (RXFP1), the cognate receptor for relaxin, is a G-protein coupled receptor (GPCR) possessing a unique extracellular region consisting of a domain of 10 leucine rich repeats (LRRs) linked to an N-terminal low density lipoprotein Class A module. Relaxin binds to its receptor primarily by a high affinity interaction with the LRRs. An additional low-affinity interaction has been proposed to occur between relaxin and the the exoloops (ELs) of the transmembrane domain, however the molecular detail of this interaction remains undefined. While site directed mutagenesis and subsequent functional characterisation of these mutants traditionally allows identification of residues contributing to receptor function, in this case results are complicated by the presence of the high affinity binding site in the LRRs. To create a tool to investigate the low-affinity interaction, a protein scaffold system displaying exoloops 1 and 2 from RXFP1 was designed. This was achieved by inserting RXFP1 exoloops 1 and 2 into the native loops of a thermostabilised 6 kDa GB1 protein creating EL1/EL2-GB1. This protein has been expressed and purified in milligram quantities and used in conjunction with biophysical techniques such as NMR to explore relaxin binding to the exoloops of RXFP1.